2020
DOI: 10.1017/dmp.2020.211
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Care Planning, Preparedness, and Response Among Rural Long-Term Care Providers

Abstract: Objective: Rural Long-term Care (LTC) providers face unique challenges when planning, preparing for, and responding to disasters. We sought to better understand challenges and identify best practices for LTC in rural areas. Methods: Case studies including key informant interviews and site visits were conducted with LTC staff and emergency planning, preparedness, and response partners in three rural communities. Themes were identified across sites using inductive coding. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Furthermore, the research findings also indicated that participants in administrative districts with a higher average service population (meaning a larger population served per medical institution) showed significantly greater improvements in grip strength of both hands after the intervention. Based on previous research findings, it could be inferred that medical service institutions in areas with scarce resources may face certain problems, such as shortages in human resources, inadequate infrastructure, policy issues, and transportation inconvenience [ 34 , 35 , 36 ], and these areas may also have lower levels of urbanization. Areas with lower levels of urbanization often experience problems such as an outflow of the young population and an increase in the elderly population, which may urgently require measures related to elderly support [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the research findings also indicated that participants in administrative districts with a higher average service population (meaning a larger population served per medical institution) showed significantly greater improvements in grip strength of both hands after the intervention. Based on previous research findings, it could be inferred that medical service institutions in areas with scarce resources may face certain problems, such as shortages in human resources, inadequate infrastructure, policy issues, and transportation inconvenience [ 34 , 35 , 36 ], and these areas may also have lower levels of urbanization. Areas with lower levels of urbanization often experience problems such as an outflow of the young population and an increase in the elderly population, which may urgently require measures related to elderly support [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the current study participants are all from long-term care facilities in rural areas. Based on past research findings, it can be inferred that there may be some issues with long-term care in rural areas, such as shortages in human resources, inadequate infrastructure, policy issues, and inconvenient transportation ( Chuakhamfoo et al, 2020 ; Radcliff et al, 2022 ; Zhu & Österle, 2017 ). In addition, the issues of outflow of the young population and aging population in rural areas may urgently require support for aging-related facilities ( Fang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…This shows that the population in Taiwan is rapidly aging. How to cope with an aging society is a pressing issue for many countries concerning the social welfare for the elderly, elderly care, elderly travel, and even crimes committed on the elderly [6][7][8][9][10].…”
Section: Research Motives 1population Aging In Taiwanmentioning
confidence: 99%